The Provision of Dental Care to COVID-19 Survivors: A Concise Review - Wei Cheong Ngeow; Liszen Tang; Jan Yang Ho; Hui Wen Tay; Raymond Chung Wen Wong; Mas Suryalis Ahmad; Vinay Marla; Karthick Sekar (Elsevier, 2022)
ABSTRACT: Aims: It has been reported that there are a certain percentage of COVID-19 patients who recover but suffer from devastating permanent organ damage or failure. Others suffer from long Covid syndrome, with prolonged symptoms that persist more than 12 weeks. However, there is scarcity of literature regarding the provision of dental treatment for these two groups of patients. This manuscript reviews the impact of multi-system involvement on the provision of dental care to these patients. Materials and methods: A search of literature was done in PubMed-Medline and Scopus databases to review the available literature on COVID-19 impacts on pulmonary, cardiovascular, haematologic, renal, gastrointestinal, endocrine, and neurologic systems and respective management in dental clinical settings. Results: The literature search from PubMed-Medline and Scopus databases resulted in 74 salient articles that contributed to the concise review on COVID-19 effects on pulmonary, cardiovascular, haematologic, renal, gastrointestinal, endocrine, and neurologic systems and/or its respective dental management recommendations. Conclusions: This concise review covers the management of post COVID-19 patients with pulmonary, cardiovascular, haematologic, renal, gastrointestinal, endocrine, or neurologic system complications.